The Development of the International Intestinal Failure Registry and an Overview of its Results - Avitzur, Yaron; Pahl, Eric; Venick, Robert; and the International Intestinal Failure Registry (European Journal of Pediatric Surgery, 2024)
Pediatric intestinal failure (IF) is a rare disease that represents an evolving field in pediatric gastroenterology and surgery. With only a limited number of multicenter collaborations, much of the research in pediatric IF is often confined to single-center reports with small sample sizes. This has resulted in challenges in data interpretation and left many knowledge gaps unanswered. Over the past two decades, five large multicenter collaborations, primarily from North America and Europe, have published their findings. Apart from one ongoing European adult and pediatric registry, these relatively large-scale efforts have been concluded.In 2018, the International Intestinal Failure Registry (IIFR) was initiated by the International Intestinal Rehabilitation and Transplant Association to continue these efforts and answer some of the knowledge gaps in pediatric IF. The IIFR goals are to prospectively assess the natural history of children diagnosed with IF and creating a worldwide platform to facilitate benchmarking and evidence-based interventions in pediatric IF. A pilot phase involving 204 enrolled patients was initiated in 2018 to assess the feasibility of an international IF registry and refine the study protocol and data collection forms. Following the successful completion of this phase, the current phase of the IIFR was launched in 2021. As of May 2023, the registry includes 362 prospectively followed children from 26 centers worldwide. This review provides an overview of the development, structure, and challenges of the IIFR, as well as the main findings from both the pilot and current phase.
Keywords: intestinal failure; registry; children; outcome; structure